2017
DOI: 10.1002/elps.201700373
|View full text |Cite
|
Sign up to set email alerts
|

Electropreconcentration‐induced local pH change

Abstract: Ion-permselective nanochannel-based sample preconcentration or electropreconcentration has been demonstrated as an effective technique for concentrating charged analytes at the interface between a micro- and nanochannel. The anion-selective electropreconcentration involves extraction of hydroxide in the preconcentrated sample plug, resulting in pH decrease. We investigated the pH change in a microchannel using charged pH indicators with different conditions including running buffer pH, sample channel electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…After the preconcentration reaches a saturated concentration, the preconcentrated sample plug size however, continues to increase, maintaining a constant sample collecting rate. This phenomenon is consistent with previously reported results [2,11,23,30]. A discontinuity point for the 1 M sample at 3 min (Fig.…”
Section: Anion Sample Preconcentrationsupporting
confidence: 94%
See 2 more Smart Citations
“…After the preconcentration reaches a saturated concentration, the preconcentrated sample plug size however, continues to increase, maintaining a constant sample collecting rate. This phenomenon is consistent with previously reported results [2,11,23,30]. A discontinuity point for the 1 M sample at 3 min (Fig.…”
Section: Anion Sample Preconcentrationsupporting
confidence: 94%
“…Glass microchip fabrication and channel coating procedures are based on previous work (see Supporting Information, Chip fabrication). Briefly, chrome/photoresist coated 10 × 10 cm 2 , 0.9 mm thick B270 glass (Telic, Valencia, CA) was used as the base substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literatures reported that the pH change could be mitigated by reducing the external electric field or increasing salt concentration in the buffer solution [40] and the surface area of electrodes [36]. To minimize pH changes in ICP device, other had demonstrated that continuous extraction of the pH changed fluid before biomolecules were blocked from passing through the ICP barrier [41].…”
Section: Introductionmentioning
confidence: 99%